Why the Germans lose at war : the myth of German military superiority - Macksey, Kenneth (London : Greenhill Books ; Mechanicsburg, PA : Stackpole Books, 1999)
"The German armed forces have suffered crushing defeat twice this century. Kenneth Macksey now examines the reasons behind these catastrophic military failures: the random fortunes of war, or the inevitable result of a particular structure, leadership and history"--Page 4 of cover.
G?tterd?mmerung at N?rnberg -- From Jena to Sedan -- Towards war on two fronts -- Verdun to Compi?gne -- Seeckt to Hitler -- The Six Years' Revolution -- Blitzkrieg in Poland -- Exultation and errors in the West -- Delusion and delays -- Multi-front war : into the Mediterranean and Balkans -- Barbarossa and degeneration -- Ill-met in Moscow -- Mediterranean diversions and strategic flaws -- Suicide in Russia -- Change of course -- The long rearguard action -- Eclipse -- Obliteration -- A fractured destiny.
Originally published: From triumph to disaster. London : Greenhill Books, 1996.
Includes bibliographical references and index.
Keywords: 1800-1999; Leadership -- History -- 19th century; History; Military history